Utilisation of Benime Application to Improve Video-Based Student Achievement - Miftachurohmah, Nisa; Guilin, Xie; Jahara, Jahara; Fusfitasari, Yenni; Ikmah, Amit Dana (Al-Hijr: Journal of Adulearn World, 2024)
The quality of students in Indonesia must be improved in education, both general education and Islamic religious education and at this time students find it difficult to understand the learning material provided by the teacher. One solution to improve student achievement at school is through the Benime application. The Benime application is a social media or platform used to create various forms of very interesting animated displays with a white background or whiteboard. The purpose of this study was to determine the benefits of the Benime application in order to improve student achievement at school. The medote used by researchers in this study is quantitative method, using surveys to students at school through google form. The results of this study are to determine the benefits of the Benime application in improving student achievement at school. The limitation of this study is that researchers only utilize the Benime application for one subject, and researchers hope that future researchers can do the same research but aim to develop the Benime application for learning videos.